Matemática, aprendizagem baseada em problemas: metodologia inovadora no 9º ano do ensino fundamental de uma escola pública - (:unkn) unknown (Universidade Federal de Goiás, 2019)
This research is about the proposal of using Problem Based Learning (PBL) as a methodology that pretends to be innovating as it contradicts traditional approaches, that, today, no longer corresponds to the students’ characteristics nor their necessities inputted by a world into constant and fast social and technological changes. The investigation had as subjects students on the 9th grade on fundamental learning at Escola Estadual do Bairro Jardim das Palmeiras, in Uberlândia/MG. The research directed of answering to the following question: is it possible that PBL becomes a math process learning that attends to the students’ necessities charged by the world and lived by them? It was developed a qualitative investigation, to verify if PBL, supported by technological resources, creates a motivational learning environment, capable of enhancing the learning construction process. The literature’s revision indicates that there are few works using PBL at math area in basic education. The methodology indicated seven steps conceived as adequate to the aim of PBL: to educate participating, critical, self-governing, capable of problem solving students, who accept different opinion, and that access data by digital resources to learn math. With PBL, the problem is the initial target to develop knowledgment, taking the student to be the responsible of building self-knowledge, and the teacher the facilitator to it. The experience of using PBL’s seven steps application, analysis and discussion at math teaching in basic education conducted to an affirmative answer to the research’s goal, as that it put in evidence that the knowledge construction provided students to act as math day-by-day problem’s solutioners. We hope that, afterwards, the result obtained into the investigation in this research encourages and serve as a parameter to other researchers, to look after new paths on teaching math.
Mathematics, problem based learning: innovative methodology in the 9th grade of elementary school in a public school
Keywords: Aprendizagem Baseada em Problemas (ABP); TIC’S; Metodologia ativa; Problem Based Learning (PBL); Active methodology; CIENCIAS EXATAS E DA TERRA::MATEMATICA